Perencanaan Pembangkit Listrik Tenaga Surya Sistem Grid- Connected Berbasis Pvsyst 6.7.0 Pada Kantor Desa Putat Kecamatan Sedong Kabupaten Cirebon - Slamet Hani; Gatot Santoso; Sigit Priyambodo; Fikri Fahrezzy (Prosiding Sains dan Teknologi, 2022)
The use of renewable energy sources is an effort to answer the challenges of the energy crisis that is occurring. One of the renewable energies is the use of solar energy. Government Regulation Number 79 of 2014 concerning national energy policies encourages the use of Renewable Energy (EBT). One of the public facilities that can be used as the object of the author's application to initiate planning for a solar power plant is the Putat Village Government Office, Sedong District, Cirebon Regency. This planning is carried out using the Pvsyst 6.7.0 software with direct data collection method. The results of calculations and analysis are obtained to meet the needs of the electrical energy load of 50,587.7 Wh in the Village Government Office of Putat requires a solar power plant capacity of 10,402 Wp or 10.402 kWp with an array area of 61.77 m2 and 48 units of solar modules with the capacity of each module solar 220 Wp, SCC requires 2 units, batteries require 52 units with a battery storage capacity of 12 volts 200 Ah and 1 inverter unit with an output power capacity of 10 kW. Keywords: solar power, power generation, Pvsyst 6.7.0